2022
DOI: 10.1161/jaha.121.024526
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Monitored Cardiac Implantable Electronic Device Data Predict All‐Cause and Cardiovascular Unplanned Hospitalization

Abstract: Background Unplanned hospitalizations are common in patients with cardiovascular disease. The “Triage Heart Failure Risk Status” (Triage‐HFRS) algorithm in patients with cardiac implantable electronic devices uses data from up to 9 device‐derived physiological parameters to stratify patients as low/medium/high risk of 30‐day heart failure (HF) hospitalization, but its use to predict all‐cause hospitalization has not been explored. We examined the association between Triage‐HFRS and risk of all‐caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Reduction in hospitalization, symptomatic improvement, and maximization of functional capacity represent the major challenges in heart failure management for the coming years. In HF patients with CIEDs, remote monitoring of implanted devices can help improve patient management through early diagnosis of heart failure events or risk stratification of cardiovascular and noncardiovascular adverse events [6,[9][10][11]. To improve the specificity of CIED remote monitoring and its ability to guide clinical decision making, an app was designed for a patient smartphone or tablet to receive information about clinical state of HF patients during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in hospitalization, symptomatic improvement, and maximization of functional capacity represent the major challenges in heart failure management for the coming years. In HF patients with CIEDs, remote monitoring of implanted devices can help improve patient management through early diagnosis of heart failure events or risk stratification of cardiovascular and noncardiovascular adverse events [6,[9][10][11]. To improve the specificity of CIED remote monitoring and its ability to guide clinical decision making, an app was designed for a patient smartphone or tablet to receive information about clinical state of HF patients during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…By means of validated multiparametric analysis, CIEDs from different manufacturers can estimate the risk of developing AHF in the subsequent month, thus allowing physicians to act at a preclinical or subclinical stage. In particular, the HF risk score (HFRS) provided by the Medtronic TriageHF TM algorithm has been validated for AHF prediction on a large cohort of patients implanted with ICD or CRT-D devices [7][8][9] and has also been shown to predict all-cause and non-HF-related cardiovascular hospitalizations [9,10] as well as all-cause mortality [11].…”
Section: Introductionmentioning
confidence: 99%
“…66 Recent real-world data from a Manchester, UK, cohort found that 60% of HF hospitalisations were preceded by a high-risk status within 30 days. 67 Beyond HF hospitalisation, recent studies have also examined the relationship between TriageHF status and all-cause mortality. One study examined data for 439 adults with TriageHF-compatible devices over a median 702-day follow-up.…”
Section: Medtronic Triagehf Risk Statusmentioning
confidence: 99%
“…There is increasing evidence from recent non-randomised and real-world studies indicating benefit. 47,67,69 Table 2 summarises HF RM platforms available in the UK.…”
Section: Current and Future State Of Playmentioning
confidence: 99%
“…This stratification highlights other research findings focusing on “high-risk score” alerts, indicating that only the high-risk status is associated with an increased risk of HF hospitalization, designating high-risk alerts as actionable. However, previous studies on the triage-HF risk algorithm’s performance have reported wide variability in its sensitivity, specificity, and positive predictive values in predicting HF hospitalizations among high-risk scores [ 12 , 22 , 23 , 24 , 25 , 26 ]. Its sensitivity ranged from 31.5% to 98.6%, its specificity from 63.4% to 90.1%, and its positive predictive values from 4.1% to 55.9%.…”
Section: Introductionmentioning
confidence: 99%